Conservation and divergence of regulatory strategies at Hox Loci and the origin of tetrapod digits. - Joost M Woltering (Public Library of Science (PLoS), 2014)
The evolution of tetrapod limbs from fish fins enabled the conquest of land by vertebrates and thus represents a key step in evolution. Despite the use of comparative gene expression analyses, critical aspects of this transformation remain controversial, in particular the origin of digits. Hoxa and Hoxd genes are essential for the specification of the different limb segments and their functional abrogation leads to large truncations of the appendages. Here we show that the selective transcription of mouse Hoxa genes in proximal and distal limbs is related to a bimodal higher order chromatin structure, similar to that reported for Hoxd genes, thus revealing a generic regulatory strategy implemented by both gene clusters during limb development. We found the same bimodal chromatin architecture in fish embryos, indicating that the regulatory mechanism used to pattern tetrapod limbs may predate the divergence between fish and tetrapods. However, when assessed in mice, both fish regulatory landscapes triggered transcription in proximal rather than distal limb territories, supporting an evolutionary scenario whereby digits arose as tetrapod novelties through genetic retrofitting of preexisting regulatory landscapes. We discuss the possibility to consider regulatory circuitries, rather than expression patterns, as essential parameters to define evolutionary synapomorphies.